Clozapine interaction with the M2 and M4 subtypes of muscarinic receptors - Michal, P; Lysíková, M; El-Fakahany, E E; Tucek, S (European journal of pharmacology, 1999)
Available evidence indicates that the antipsychotic drug clozapine acts as a partial agonist at the muscarinic M4 and as an antagonist at the M2 receptors. We wondered whether there is indeed a fundamental difference between its action on these two receptor subtypes, and whether it interacts with their classical or allosteric binding sites. In experiments on Chinese hamster ovary cells stably expressing the M2 or M4 receptors, clozapine inhibited the binding of the specific muscarinic ligand [3H]N-methylscopolamine to either receptor subtype. The affinity of the high-affinity sites for clozapine was diminished by GTP in the way expected for agonists on both the M2 and the M4 receptor subtypes. Arunlakshana-Schild plots of data obtained in saturation binding experiments with [3H]N-methylscopolamine at different concentrations of clozapine were linear with a slope of unity. Clozapine did not alter the time course of [3H]N-methylscopolamine dissociation from muscarinic M2 or M4 receptors. It inhibited the synthesis of cyclic AMP in cells expressing the M4 receptor subtype, but did not measurably inhibit the synthesis of cyclic AMP in cells expressing the M2 receptor subtype. We conclude that clozapine has a high affinity for muscarinic M2 and M4 receptor subtypes, that it associates with the classical and not with the allosteric binding site, and that it acts as a partial agonist on both the M2 and the M4 receptor subtype.
Keywords: Allosteric Regulation; Clozapine; Muscarinic Agonists; Receptor, Muscarinic M2; receptory muskarinové; AMP cyklický; ligandy; Cyclic AMP; CHO Cells; antagonisté muskarinových receptorů; Ligands; receptor muskarinový M2; receptor muskarinový M4; N-methylskopolamin; agonisté muskarinových receptorů; Cricetinae; alosterická regulace; Animals; CHO buňky; zvířata; N-Methylscopolamine; karbachol; Antipsychotic Agents; Carbachol; Receptors, Muscarinic; Receptor, Muscarinic M4; klozapin; křečci praví; antipsychotika; Muscarinic Antagonists